DNA methylation differences in monozygotic twins with Van der Woude syndrome - Petrin, A. L.; Zeng, E.; Thomas, M. A.; Moretti-Ferreira, D.; Marazita, M. L.; Xie, X. J.; Murray, J. C.; Moreno-Uribe, L. M. (Frontiers in Dental Medicine, 2023)
Van der Woude Syndrome (VWS) is an autosomal dominant disorder responsible for 2% of all syndromic orofacial clefts (OFCs) with IRF6 being the primary causal gene (70%). Cases may present with lip pits and either cleft lip, cleft lip with cleft palate, or cleft palate, with marked phenotypic discordance even among individuals carrying the same mutation. This suggests that genetic or epigenetic modifiers may play additional roles in the syndrome’s etiology and variability in expression. We report the first DNA methylation profiling of 2 pairs of monozygotic twins with VWS. Our goal is to explore epigenetic contributions to VWS etiology and variable phenotypic expressivity by comparing DNAm profiles in both twin pairs. While the mutations that cause VWS in these twins are known, the additional mechanism behind their phenotypic risk and variability in expression remains unclear. We generated whole genome DNAm data for both twin pairs. Differentially methylated positions (DMPs) were selected based on: (1) a coefficient of variation in DNAm levels in unaffected individuals < 20%, and (2) intra-twin pair absolute difference in DNAm levels >5% (delta beta > | 0.05|). We then divided the DMPs in two subgroups for each twin pair for further analysis: (1) higher methylation levels in twin A (Twin A > Twin B); and (2) higher methylation levels in twin B (Twin B >Twin A). Gene ontology analysis revealed a list of enriched genes that showed significant differential DNAm, including clef-associated genes. Among the cleft-associated genes, TP63 was the most significant hit (p=7.82E-12). Both twin pairs presented differential DNAm levels in CpG sites in/near TP63 (Twin 1A > Twin 1B and Twin 2A < Twin 2B). The genes TP63 and IRF6 function in a biological regulatory loop to coordinate epithelial proliferation and differentiation in a process that is critical for palatal fusion. The effects of the causal mutations in IRF6 can be further impacted by epigenetic dysregulation of IRF6 itself, or genes in its pathway. Our data shows evidence that changes in DNAm is a plausible mechanism that can lead to markedly distinct phenotypes, even among individuals carrying the same mutation.